ADAPTATION OF MARKETING STRATEGIES TO THE MENTAL AND BEHAVIORAL CHARACTERISTICS OF THE TARGET AUDIENCE - Voloshko, Liudmyla (Modern engineering and innovative technologies, 2025)
The article is dedicated to the study of adapting marketing strategies to the mental and behavioral characteristics of the target audience. The aim of the study is to identify the main approaches to creating effective adaptive marketing strategies that ta